Professional Education in Built Environment & Design. - Savage, Susan; Betts, Martin; Bow, Louise; Davis, Rebekah; Miller, Evonne (Australian Learning and Teaching Council (ALTC), 2010)
Project Findings: This project commenced with the aim of scoping the challenges facing built environment and design (BED) education. It focused on new graduates by canvassing their views and those of academic staff and professional practitioners on the transition-to-work experience. The study makes recommendations about how the variations in transition experience across a range of worksites may be better understood and supported. The singular challenge for most parties centres on the ways in which courses prepare graduates for the pace, diversity and flux of contemporary professional practice. The study proceeded through literature review, focus group interviews, national online survey and workshops. It found further evidence of the importance of higher-order graduate capabilities, and the development of emotional intelligence. In the light of these findings, the study recommends the establishment of a national good practice guide and network to help ensure that the transition-to-work of BED graduates is supported and sustained across the sector; conduct of a national conversation about transition-to-work for BED graduates to help shape policy and practice; and the development and implementation of a range of transition-to-work strategies to ameliorate negative effects of the transition experience and to promote its importance to the professions and young BED professionals.